L’egemonia e i “subalterni”: utopia, religione, democrazia - Frosini, Fabio (International Gramsci Journal, 2023)
My contribution is divided into four sections. The first is devoted to an illustration of what I shall call “post-Jacobin” hegemony in the Prison Notebooks. The starting point is, therefore, the attempt to demonstrate the presence in the Notebooks, of not one but two notions of hegemony. The first of these – the “Jacobin” one – corresponds to the passage from the economic-corporative to the hegemonic and to the primacy of “culture”. The second, belonging to the mass and standardized society of the 1920s and 1930s, appears as an indissoluble intertwining of progressive and regressive aspects, summarized in the oxymoron “passive revolution”. The second section focuses on this new situation, characterized by a sort of “double” or reciprocal siege – that of the masses besieging the State and vice versa – and hence by a polarity constituted by bureaucratization and democratization, as two aspects which are both present in the “capillary” and “diffused” hegemony at work in the societies that emerged from World War I. The third section concentrates on the ideological conditions in which the new hegemonic struggle takes place. In them, religion, in as much as it is a form of massive contact between the rulers and the ruled, takes on a decisive role, both as a form of government and as a mode of resistance. Lastly, the fourth section, by focusing on Gramsci’s reflections on the concept of “myth” as a grammar of mass politics, explores the eventual connections between myth and democracy, thereby connecting the arguments dealt with respectively in the second and third sections.